2013
DOI: 10.1126/scitranslmed.3006258
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Receptor Antagonists Including Caffeine Alter Fetal Brain Development in Mice

Abstract: pregnancy.longitudinal prospective human studies will be needed to evaluate the consequences of caffeine consumption during effects of adenosine receptor antagonists including caffeine on brain development in humans. Retrospective and neuronal types as well as impaired memory on certain types of memory tests. This study raises questions about the that adult offspring of pregnant mice treated with adenosine receptor antagonists had reduced numbers of certain antagonists were more susceptible to seizures when ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
125
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(155 citation statements)
references
References 78 publications
16
125
1
3
Order By: Relevance
“…Prophylactic studies with caffeine or KW6002 were done using previously validated doses (14,40). Mice were divided into two groups: a drug-free group drinking water or vehicle and a treated group drinking either 1 g/L caffeine (Sigma), starting 3 wk before CUS, or KW6002 (istradefylline; 3 mg/kg, dissolved in 0.5% nitrocellulose), synthesized as described previously (41), starting 4 d before CUS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylactic studies with caffeine or KW6002 were done using previously validated doses (14,40). Mice were divided into two groups: a drug-free group drinking water or vehicle and a treated group drinking either 1 g/L caffeine (Sigma), starting 3 wk before CUS, or KW6002 (istradefylline; 3 mg/kg, dissolved in 0.5% nitrocellulose), synthesized as described previously (41), starting 4 d before CUS.…”
Section: Methodsmentioning
confidence: 99%
“…Anhedonic-like behavior was evaluated with the sucrose (1.2%) preference test (44) by measuring the intake of sucrose solution versus water intake at the end of a 16-h test period (12-h dark phase plus 4-h light phase) or with the splash test by measuring grooming bouts (head washing and nose/face and body grooming) over 5 min after a 10% sucrose solution was squirted on the dorsal coat (45). Social recognition memory was evaluated as previously described (39), and spatial memory was evaluated using an object-displacement test (40), a reference memory version of the Morris water maze (46), and a two-trials Y-maze test in which mice first explored the maze for 8 min while one arm was blocked and explored it again 2 h later for 8 min with all three arms accessible (14). Behavioral experiments were conducted between 10:00 AM and 5:00 PM in a sound-attenuated room under low-intensity light and were monitored by two researchers who were unaware of phenotypes or drug treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Date seed presented an interesting antioxidant capacity to scavenging DPPH free radicals and it seems to be used in food as an important antioxidant source. For example, caffeine is the active ingredient found in coffee beans (Coffea), showing biological activity in the treatment of central nervous system (CNS) disorders [23][24].…”
Section: Free Radical Scavenging: Test Dpphmentioning
confidence: 99%
“…Caffeine intake is negatively associated with gestational changes in animals, such as lower rates of fertilization and embryonic implantation, low birth and placental weight, greater number of stillbirths, increased expression of apoptotic markers and altered placental and bone formation [9,27,[40][41][42][43][44][45][46] ( Table 1).…”
Section: Caffeine and Pregnancymentioning
confidence: 99%
“…Elmazar and colleagues [42] induced caffeine consumption in albino female mice intraperitoneally and orally, and described increased circulating corticosterone and cleft palate in litters, although no detection of reduced utero-placental or placental-fetal blood flow were reported at 14 GD. Silva and colleagues [43], exposing female mice to oral doses of 0.3 g/liter of caffeine (diluted in water), suggested that caffeine exposure by mouse pups during gestation and lactation had deleterious effects on neuronal development, hyper excitable hippocampus, susceptibility to seizures and cognitive deficits that could remain even in adult life. Serapiao-Moraes and colleagues [44] using C57BL/6 pregnant mice, with daily subcutaneous caffeine doses of 20 mg/kg, reported negative outcomes in adult offspring from treated mothers.…”
Section: Caffeine Intake During Pregnancy: What Are the Real Evidences?mentioning
confidence: 99%